PENERAPAN GOOD GOVERNANCE DALAM PELAYANAN PERIZINAN DI KOTA DUMAI - Adianto, Adianto; Mayarni, Mayarni; Mashur, Dadang (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
The Government was formed with the intention to build a civilization and maintaining social order system so that people can live their lives reasonably within the context of the life of the State. In the process, the concept of the Government is experiencing a transformation of the paradigm of the Department of State to the orientation of the market (market or public interest), of a strong Government, large and small otoritarian to the orientation and less government, egalitarian and democratic, as well as the transformation of the system of governance of the implementation to desentralistik. The Organization of good governance is the Foundation for the preparation and implementation of the policy of a democratic State in the era of globalization. The phenomenon of democracy is marked by the rise of community control against the conduct of the Government, as in the 56th Government, development and public service. This study examines in a comprehensive manner about the application of the principles of good governance in the service of licensing in the city of Pekanbaru and Dumai, in factors that inhibit and supports the application of good governance in the service of licensing in Dumai. Results of the study found that the public approved the application of the principles of good governance in the service of licensing conducted by the Agency of Integrated Services and capital investment (BPTPM) Dumai. The application of the licensing services in the Agency's Integrated Services and capital investment (BPTPM) have started to Dumai based with good governance, which in practice is still running quite well.